Pengaruh Beban Kerja dan Motivasi Kerja terhadap Kepuasan Kerja Karyawan PT CityNeon Prima Mandiri - Siti Toipah; Joko Ariawan (Jurnal Bintang Manajemen, 2025)
This study aims to determine the effect of workload and work motivation variables on employee job satisfaction at PT CityNeon Prima Mandiri partially and simultaneously. Where a problem phenomenon was found related to the decline in job satisfaction of PT CityNeon Prima Mandiri employees, which is one of the important factors in influencing the course of the company’s activities as a whole. The research method used in this study is the quantitative statistical method. The sample in this study used the entire population sampled with a total of 36 employees of PT CityNeon Prima Mandiri. The data collection technique used was a likert-scale questionnaire. The results of the study showed that partially workload had a negative and significant effect on job satisfaction with a calculated t of -6.656 > t table 2.034 and sig. 0.000 < 0.05. In addition, work motivation had a positive and significant effect on job satisfaction with a calculated t of 2.799 > t table 2.034 and sig. 0.008 < 0.05. Simultaneously, workload and work motivation affect job satisfaction with f count 28.653 > f table 4.139 and sig. 0.000 < 0.05.